The Effectiveness of the ABC Theory-Based Intervention Program on Academic Anxiety and Psychological Resilience of Female Students of Ibnu Katsir 2 Jember (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
Psychological Resilience Based on ABC Theory in Overcoming Academic Anxiety in Ibnu Katsir 2 Female Students of Jember. This study aimed to test the effectiveness of an intervention program based on the ABC (Activating Event, Belief, Consequence) theory, developed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, in reducing academic anxiety and increasing psychological resilience in female students. The method used was a quasi-experimental pretest-posttest design in one group. The study sample consisted of female students who demonstrated high levels of academic anxiety based on initial assessment results. The intervention was implemented through several structured group counseling sessions designed to change irrational beliefs and strengthen adaptive skills. Data analysis using a paired t-test revealed a significant difference between pretest and posttest scores for both academic anxiety and psychological resilience (p < 0.05). These findings indicate that the ABC theory-based intervention is effective in addressing common psychological problems faced by students. The implication of this study is the importance of integrating a cognitive-behavioral approach into guidance and counseling services in religious higher education settings. It is recommended that campuses and Islamic boarding schools provide ongoing support for the implementation of similar programs to create a mentally and emotionally healthier learning environment for students.Keywords: ABC Theory, Academic Anxiety, Psychological Resilience, Female